Kontekstulisasi Kisah Nabi Yusuf Bagi Generasi Milenial - Rifangi, Fuad (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2022)
The results of the study concluded that in the journey of the prophet, the story of Yusuf from when he was a child to an adult which Allah has explained in Surah Yusuf has figure values ​​that we can apply, especially for the millennial generation, including: first, the educational value of the prophet Ya'qub to Prophet Yusuf. Second, Youth who have a sense of optimism in dealing with problems. Third, young people who are patient and strong. Patience in the form of patience from the exile of his brothers, the patience of the prophet Yusuf when he was a slave, patience when he was in the custody of Zulaikha, patience when slandered and imprisoned. Fourth, the leadership attitude of the prophet Yusuf, namely a leader who is not vindictive and a humble leader. So for the millennial generation if you want to get success and success in both the world and the hereafter, you must have faith, patience, optimism, and trust in Allah subhanahu wata'ala, never give up and always cultivate abilities and skills and be controlled correctly and precisely.